2012
DOI: 10.1002/acr.20642
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes and costs of an integrated rehabilitation program for chronic knee pain: A pragmatic, cluster randomized, controlled trial

Abstract: Objective. Chronic joint pain is a major cause of pain and disability. Exercise and self-management have short-term benefits, but few studies follow participants for more than 6 months. We investigated the long-term (up to 30 months) clinical and cost effectiveness of a rehabilitation program combining self-management and exercise: Enabling SelfManagement and Coping of Arthritic Knee Pain Through Exercise (ESCAPE-knee pain). Methods. In this pragmatic, cluster randomized, controlled trial, 418 people with chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
223
3
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(240 citation statements)
references
References 46 publications
(68 reference statements)
10
223
3
4
Order By: Relevance
“…This was supported by a large RCT published by Hurley et al 3 , which reported that exercise and selfmanagement for 6 weeks only had a high probability (80e100%) of being cost-effective at 30 months. Four hundred and eighteen patients with chronic knee pain met the inclusion criteria and were assigned to either the exercise and self-management group or the control group (usual care).…”
Section: Exercise Is Cost-effectivenessmentioning
confidence: 68%
“…This was supported by a large RCT published by Hurley et al 3 , which reported that exercise and selfmanagement for 6 weeks only had a high probability (80e100%) of being cost-effective at 30 months. Four hundred and eighteen patients with chronic knee pain met the inclusion criteria and were assigned to either the exercise and self-management group or the control group (usual care).…”
Section: Exercise Is Cost-effectivenessmentioning
confidence: 68%
“…Whilst it is a very recent development, early study of the brace looks promising: it effectively appears to decrease levels of internal abduction, which is a major contributor to the compressive forces through the joint. This may lead, as it did immediately in some of the study patients, to reduced pain whilst wearing the device during walking [53,54]. There is, of course, the need for more in-depth study of the characteristics and effects of the brace, though it may become an attractive management plan to delay the need for THR.…”
Section: Hip Bracesmentioning
confidence: 99%
“…A recent RCT has contributed to current knowledge in this area. In a pragmatic cluster RCT in 418 people with chronic knee pain [11], long-term clinical and cost benefits were found 30 months after the completion of a rehabilitation program that combined self-management and exercise. The authors reported improvements in symptoms, as well as reductions in community-based health care costs, medication costs, and total health and social care costs, compared to usual care.…”
Section: Exercise Is Integral In Managing Knee Oamentioning
confidence: 99%